2022
DOI: 10.1093/neuonc/noac107
|View full text |Cite
|
Sign up to set email alerts
|

Decitabine increases neoantigen and cancer testis antigen expression to enhance T-cell–mediated toxicity against glioblastoma

Abstract: Background Glioblastoma (GBM) is the most common and malignant primary brain tumor in adults. Despite maximal treatment, median survival remains dismal at 14–24 months. Immunotherapies, such as checkpoint inhibition, have revolutionized management of some cancers but have little benefit for GBM patients. This is, in part, due to the low mutational and neoantigen burden in this immunogenically “cold” tumor. Methods U87MG and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…By boosting the activation of the mammalian target of rapamycin complex 2, rapamycin, another drug candidate discovered, may be used to reduce inflammation in patients with heart disease [ 66 ]. Meanwhile, another drug, decitabine, could increase neoantigen expression to enhance T cell-mediated toxicity against glioblastoma [ 67 ]. Testosterone enanthate replacement therapy is commonly used in patients with low testosterone [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…By boosting the activation of the mammalian target of rapamycin complex 2, rapamycin, another drug candidate discovered, may be used to reduce inflammation in patients with heart disease [ 66 ]. Meanwhile, another drug, decitabine, could increase neoantigen expression to enhance T cell-mediated toxicity against glioblastoma [ 67 ]. Testosterone enanthate replacement therapy is commonly used in patients with low testosterone [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, clinical attempts to treat newly diagnosed and recurrent GBM with epigenetic inhibitors (plus chemoradiation and surgery) have had negligible anti-tumor effects compared to standard-of-care treatment alone ( 186 191 ). However, preclinical studies investigating the immune effects of epigenetic inhibitors demonstrate increased immunogenicity, indicating that combining epigenetic and immunostimulatory treatment modalities may have potent anti-tumor effects ( Table 3 ) ( 17 , 44 , 46 , 104 , 185 ). Two early phase clinical trials combining anti-PD1 checkpoint inhibitors with azacytidine (DNA methyltransferase inhibitor) or vorinostat (HDAC inhibitor) plus standard chemoradiation are currently underway in IDH-mutant gliomas (NCT03684811) and newly diagnosed GBM (NCT03426891), respectively.…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
“…Thus, strategies for targeting immune suppressive mechanism specifically within the TME while avoiding counterproductive systemic effects are needed. Despite these early phase results, the immunogenic effects of epigenetic inhibitors and combo epigenetic-immune therapy in preclinical GBM studies are promising ( 17 , 44 , 46 , 104 , 185 , 192 ) and deserve to be explored to their full extent in clinical trials. Notably, increased immune recognition and resultant cytolysis of tumor cells by T cells and NK cells has been achieved through HDAC inhibitors and DNA hypomethylating agents (e.g., decitabine) ( 44 , 46 , 104 , 185 ).…”
Section: Therapeutic Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to global demethylation, some studies point to DAC leading to the inhibition of NMD [ 101 ], which, as discussed earlier in this review, triggers the stabilization of aberrant mRNAs leading to the emergence of a potential array of neoantigens. Recently, a novel study showed that treatment with DAC in glioblastoma, a tumor with a really low TMB, induces the presentation of MHC-I-dependent neoantigens [ 102 ], demonstrating the high potential of epigenetic drugs in cancers with low mutational levels. The researchers treated patient-derived glioblastoma cells with DAC and co-cultured them with tumor-infiltrating lymphocytes (TILs) isolated from patients ex vivo, showing a significant immune reactivity boost when tumor cells were treated with DAC.…”
Section: Main Approaches To Enhance Tumor Antigenicitymentioning
confidence: 99%